Green synthesis of soluble graphene in organic solvent via simultaneous functionalization and reduction of graphene oxide with urushiol. (June 2020) - Cheng, Hongyang; Lin, Jianrong; Su, Yanning; Chen, Denglong; Zheng, Xuelin; Zhu, Hu
Highlights: Reduction of GO with urushiol under mild conditions without aid of any other stabilizers/surfactants. Urushiol with unsaturated long alkyl chain was modified on the surface of UrGO. UrGO exhibited good dispersion in a variety of organic solvents. Abstract: The poor dispersion and weak interfacial interaction are the main problems in the graphene based polymer composites. The complicated modification of graphene is usually needed. In this paper, a green and facile method is reported for the synthesis of functionalized reduced graphene oxide under mild conditions. The proposed method is based on the simultaneous reduction and surface function of graphene oxide by urushiol extracted from the sap of lacquer trees. The presence of the unsaturated long alkyl chains of urushiol not only improves the dispersion of resultant graphene in various organic solvents, but also makes graphene easily form covalent connection with polymer matrix. These features endow this urushiol functionalized graphene with great potential in the construction of graphene based polymer composites.